PENGARUH PENDIDIKAN DAN PELATIHAN PENGGUNA, KEMAMPUAN TEKNIK PEMAKAI, MOTIVASI MANAJER PUNCAK, DAN UKURAN ORGANISASI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI: STUDI KASUS PADA INDOMARET DAN ALFAMART SE-KECAMATAN KARTASURA - Rifqi, Putra Faiz; Arifin, Atwal (LP2M Universitas Bina Bangsa, 2025)
Accounting information system performance is an assessment carried out on the implementation of the accounting information system applied to a company to see the achievement of goals in accordance with the responsibility and authority in providing accounting information. This study aims to determine the influence of user education and training, user technical ability, top manager motivation, and organizational size on the performance of accounting information systems. This study uses a quantitative method. The population in this study is all employees who work at Indomaret and Alfamart in Kartasura sub-district. The sampling technique in this study uses a purposive sampling technique. The results showed that the variables of user education and training and organizational size had an effect on the performance of the accounting information system, the technical ability of users and the motivation of the top manager had no effect on the performance of the accounting information system